24th International Symposium on Research in Attacks, Intrusions and Defenses 2021
DOI: 10.1145/3471621.3471858
|View full text |Cite
|
Sign up to set email alerts
|

Living-Off-The-Land Command Detection Using Active Learning

Abstract: In recent years, enterprises have been targeted by advanced adversaries who leverage creative ways to infiltrate their systems and move laterally to gain access to critical data. One increasingly common evasive method is to hide the malicious activity behind a benign program by using tools that are already installed on user computers. These programs are usually part of the operating system distribution or another user-installed binary, therefore this type of attack is called "Living-Off-The-Land". Detecting th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Finally, Ongun et al [30] adopt active learning and cmd2vec feature generation to expand the detection range to LotL threats, which encompass attacks with more system preinstallation tools and commands. Sunoh Choi [31] provides another perspective in turning detection into a graph inference problem using GNN and an adjacency matrix generation method via Jaccard similarity to detect malicious PowerShell.…”
Section: A Detection Of Malicious Powershellmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Ongun et al [30] adopt active learning and cmd2vec feature generation to expand the detection range to LotL threats, which encompass attacks with more system preinstallation tools and commands. Sunoh Choi [31] provides another perspective in turning detection into a graph inference problem using GNN and an adjacency matrix generation method via Jaccard similarity to detect malicious PowerShell.…”
Section: A Detection Of Malicious Powershellmentioning
confidence: 99%
“…On the other hand, recently emerging techniques such as Machine Learning (ML) and Deep Learning (DL) have shown that they could offer researchers alternative solutions [18]- [21] for developing cutting-edge methods to combat cybersecurity challenges. In general, several studies achieve better performance than traditional signature scanning and execution monitoring mechanisms, including detection with vector representation features from Abstract Syntax Tree (AST) [22]- [26], Natural Language Processing (NLP) [27]- [30], and Graph Neural Network (GNN) [31] inference to differentiate between malicious and benign scripts. However, to the best of our knowledge, previous studies by ML and DL cannot be considered conclusive as they mainly focus on binary classification that discriminates malicious PSCmds from benign ones, and often fail to reveal semantics or malicious intent behind the obfuscated PSCmds.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, spotting their execution does not automatically constitute malicious activity. Further enhancing methodologies using machine learning and artificial intelligence have been proposed in [56] aiming to reduce the noise and extract useful alerts. Finally, Microsoft's Sysmon [57] is used to further enhance fileless attacks detection and prevention by monitoring for specific event IDs.…”
Section: Test Environment and Implementationmentioning
confidence: 99%
“…For this task we propose a local anomaly detection module at each client, which will be trained on the unlabeled client data in order to detect the highest ranked anomalies. Prior work [7], [48], [49] shows that anomaly detection can find new malicious behavior in unlabeled data, and we leverage this observation in our design. In addition, we also select samples for labeling from the top ranked HTTP log events obtained with the current global model at each client.…”
Section: Global Model Training For Http Malware Detectionmentioning
confidence: 99%